Antifungal and Anti-Inflammatory Activities of PS1-2 Peptide against Fluconazole-Resistant Candida albicans - Jong-Kook Lee; Soyoung Park; Young-Min Kim; Taeuk Guk; Jong Kwon Choi; Jin-Young Kim; Min-Young Lee; Mi-Kyeong Jang; Seong-Cheol Park (MDPI AG, 2022)
Clinically, fungal pneumonia rarely occurs in adults, and invasive fungal infections can cause substantial morbidity, and mortality due to sepsis and septic shock. In the present study, we have designed peptides that exhibit potent antifungal activities against fluconazole-resistant Candida albicans in physiological monovalent, and divalent ionic buffers, with minimal fungicidal concentrations ranging from 16 to 32 µM. None of these tested peptides resulted in the development of drug resistance similar to fluconazole. Among them, the PS1-2 peptide did not induce stimulation of macrophages by C. albicans, and it exerted antifungal and anti-inflammatory effects against C. albicans-induced intratracheal infection, in an acute lung injury mouse model. PS1-2 is likely a novel therapeutic agent for the control, and prevention of drug-resistant C. albicans infection, and our findings may be useful for designing antimicrobial peptides to combat fungal infection.